Electrochemical Preparation of Recycled Self-Compacting Concrete Composite Beams and Their Application in Prefabricated Buildings - Yuan Yuan; Yongchao Zhu (Journal of Chemistry)
In order to solve the problems of electrochemical preparation of recycled self-compacting concrete composite beams and their application in prefabricated buildings, we need to meet the requirements of national housing industrialization and green buildings, make up for the low development capacity of prefabricated buildings, and improve the speed of housing construction and the rapid development of the construction industry. Now the prefabricated building has entered a period of rapid growth. However, the research on the construction technology of the prefabricated building is still in its infancy, and there are many difficulties and challenges in the construction. The deformation and internal force of a prefabricated residential laminated floor slab in the construction process of prestressed PK slab transportation, stacking, hoisting, and the laminated cast-in-situ layer will affect the normal use of the building. However, at present, there is less mechanical analysis of its construction process, so there is blindness in the formulation, implementation, and inspection of the construction scheme. Through the social survey of 200 people, 179 people believe that prefabricated buildings will be better than traditional buildings. Therefore, by participating in the practice of prefabricated housing engineering, the key mechanical problems in the construction of the composite floor slab of prefabricated housing are explored and found.